Distributed ADMM power optimal control for standalone hybrid generation systems - Wei, Tengfei; Wang, Yiyang; Yang, Jichang (Frontiers in Energy Efficiency, 2024)
With the rapid development and increased demand for renewable energy sources, stand-alone hybrid generation systems have become an essential energy solution. Power optimization control becomes critical to achieving efficient operation and stability of this system. The distributed ADMM-based (Alternating Direction Method of Multipliers, ADMM) approach has the full potential to deal with the power optimization problem of stand-alone hybrid generation systems. This paper uses an optimization algorithm with a Gaussian penalty function, ADMM-ρ, to alternately optimize the power reference values of wind, light, and battery-containing power generation subsystems. The local controller controls the output power of the converter according to this reference value so that the wind and photovoltaic power generation subsystem work in the load tracking mode or the maximum power tracking mode so that the optimal operation of the hybrid power generation system meets the balance of supply and demand while prolonging the service life of the batteries; It seems that the distributed ADMM algorithm is reliable in addressing the power optimization challenge of hybrid power generation systems, as per the results of simulation experiments.